Gastrin activates nuclear factor κB (NFκB) through a protein kinase C dependent pathway involving NFκB inducing kinase, inhibitor κB (IκB) kinase, and tumour necrosis factor receptor associated factor 6 (TRAF6) in MKN-28 cells transfected with gastrin receptor. Issue 6 (1st June 2003) - Ogasa, M; Miyazaki, Y; Hiraoka, S; Kitamura, S; Nagasawa, Y; Kishida, O; Miyazaki, T; Kiyohara, T; Shinomura, Y; Matsuzawa, Y
Abstract : Background: We previously reported that gastrin induces expression of CXC chemokines through activation of nuclear factor κB (NFκB) in gastric epithelial cells that express gastrin receptor. Aims: To clarify gastrin receptor mediated signals leading to activation of NFκB. Methods: MKGR26 cells were created by transfecting gastrin receptor cDNA into MKN-28 cells. Degradation of inhibitor κB (IκB) and phosphorylation of protein kinase C (PKC)-δ were both detected by western blot analysis. NFκB activation was determined by luciferase assay and electrophoretic mobility shift analysis. Results: Gastrin induced degradation of IκB-α and activation of NFκB, which was abolished by the selective gastrin receptor antagonist L-740, 093 and the general PKC inhibitor GF109203X. Gastrin induced phosphorylation of PKC-δ, and its inhibitor rottlerin partially suppressed NFκB activation. However, the mitogen activated protein kinase (MAPK) kinase inhibitor PD98059, p38 MAPK inhibitor SB203580, and tyrphostin AG1478 had no effect on NFκB activation. Introduction of the dominant negative mutant of IκB kinase, of NFκB inducing kinase, and of tumour necrosis factor receptor associated factor 6 (TRAF6), but not that of TRAF2, inhibited gastrin induced activation of NFκB. Conclusions: Gastrin activates NFκB via a PKC dependent pathway which involves IκB kinase, NFκB inducing kinase, and TRAF6.